Mathematical modeling of the kinetics of a single intake of ethanol - G. V. Nedugov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
The aim of the study is to construct a kinetic equation of zero-order ethanol elimination with first-order absorption, taking into account the presystemic metabolism of ethanol, with the possibility of determining the errors in estimating the parameters of the model, as well as the implementation of the model in the format of a computer program. Analytical mathematical modeling of the kinetics of a single oral intake of ethanol has been performed. A mathematical model of the kinetics of a single intake of ethanol with its zero-order elimination, absorption and first-order presystemic metabolism has been developed. A method is proposed for estimating the limiting absolute errors of the kinetic parameters of the constructed model based on the summation of the partial contributions of the initial physical quantities. The complex of the developed computational procedures is implemented in the format of the «Alcohol Calculator V 1.0» computer program. The conclusion is made about the expediency of using the developed information and computing technology in the forensic medical expert assessment of acute alcohol intoxication.